ECONOMIC BASIS OF PRODUCTION OF RESOURCE EFFICIENT BUILDING MATERIALS AND NETWORK EFFICIENCY (Marketing Journal, 2025)
The article analyzes the economic foundations and efficiency of the construction materials industry in Uzbekistan with an emphasis on resource -saving technologies. Based on 2015 –2024 data, the study identifies trends in production growth, reduced energy co nsumption, and increased labor productivity. The findings indicate that a 15% reduction in energy use and a rise in recycled raw materials contribute to lower production costs and higher profitability for enterprises.
Keywords: resource efficiency; construction materials; productivity; energy saving; economic development; sustainability